A single institution experience of extranodal natural killer/T cell lymphoma of nasal type. Issue 1 (January 2015) - Khan, Luluel; Hodgson, David; Sun, Alex; Gospodarowicz, Mary; Crump, Michael; Kuruvilla, John; Pintilie, Melania; Tsang, Richard
Abstract Extranodal natural killer/T cell lymphoma (ENKTL) nasal type is a rare form of non-Hodgkin lymphoma that is more commonly seen in Asia and Latin America than in North America or Europe. The purpose of this study was to determine the treatment outcomes with a combined modality approach and whether treatment outcomes varied according to ethnicity in patients with ENKTL, nasal type in Toronto, Canada. Patients presenting with ENKTL, nasal type, between 1994 and 2011 were retrospectively reviewed. Patient characteristics, including the patient's ethnic origin, treatment details and outcomes were recorded and analyzed for significant differences between Asian and Caucasian patients. A total of 34 patients were identified: 16 Asian, 16 Caucasian, one Aboriginal and one Hispanic. All patients had nasal cavity involvement. The majority had localized disease: stage I (n = 22), stage II (n = 6); and stage IV in six patients. Combined radiotherapy (RT) and chemotherapy was intended for 32 of the 34 patients, with two receiving RT alone. Median RT dose was 45 Gy (range: 35–50.4 Gy). Response to initial treatment was observed in 44% of patients. Two-year disease-free survival was 17.8% (Asian patients: 18.8%, Caucasians: 20%, p = 0.82), and overall survival 39.2% (Asian patients: 30%, Caucasians: 42%, p = 0.52). There were no significant differences in clinical outcomes in terms of patient ethnicity. A combined modality approach (with cyclophosphamide, doxorubicin, vincristine, prednisone [CHOP] chemotherapy administered initially) is of limited effectiveness. We have now adopted the use of RT as the initial treatment approach, followed by multiagent chemotherapy.